Ingredient Functionality in Multilayered Dough-margarine Systems and the Resultant Pastry Products: A Review. Issue 13 (2nd October 2016) - Ooms, Nand; Pareyt, Bram; Brijs, Kristof; Delcour, Jan A.
ABSTRACT: Pastry products are produced from heterogeneous multilayered dough systems. The main ingredients are flour, water, fat and sugar for puff pastry, and the same plus yeast for fermented pastry. Key aspects in pastry production are (i) building laminated dough containing alternating layers of dough and bakery fat and (ii) maintaining this multilayered structure during processing to allow for steam entrapment for proper dough lift during baking. Although most authors agree on the importance of gluten and fat for maintaining the integrity of the different layers, detailed studies on their specific function are lacking. The exact mechanism of steam entrapment during dough lift and the relative contribution of water set free from the fat phase during baking also remain unclear. This review brings together current knowledge on pastry products and the factors determining (intermediate) product quality. Its focus is on flour constituents, fat, water, and (where applicable) yeast during the different production stages of pastry products. Future research needs are addressed as the knowledge on biochemical and physical changes occurring in flour constituents and other ingredients during pastry production and their effect on product quality is currently inadequate.